Batasan Intervensi Mertua dalam Rumah Tangga Anak Perspektif Hukum Keluarga Islam - Muh. Tahir; Agus Muchsin; Muhiddin Bakri (Lembaga Yasin AlSys, 2026)
Although family dynamics have been widely studied, research that specifically discusses the limits of parents-in-law’s intervention in their children’s households from the perspective of Islamic family law remains limited. This study aimed to identify forms of parents-in-law’s intervention, analyze their limits based on rights and obligations in Islamic family law, and evaluate their impact on family independence. This study used a qualitative approach with a normative juridical design supported by limited empirical data. The research participants consisted of 10 married couples selected using purposive sampling. Data were collected through semi-structured interviews and literature study, and were then analyzed using thematic analysis. The results showed that parents-in-law’s intervention generally occurred in family decision-making, economic management, and child-rearing patterns. Excessive intervention tended to reduce couples’ autonomy and trigger conflict within the household. From the perspective of Islamic family law, such intervention may conflict with the principle of qawwāmah and the wife’s right to proper housing (haq al-maskān) when it exceeds the limits of advice. These findings emphasize the importance of balancing the obligation to be dutiful to parents (birr al-wālidayn) and the independence of the nuclear family. Thus, this study contributes to the development of Islamic family law studies by offering a clarification of the limits of parents-in-law’s intervention so that interfamily relations remain harmonious, just, and do not disrupt the autonomy of the children’s household.